In-vivo evaluation of an in situ polymer precipitation delivery system for a novel natriuretic peptide - Venkatraman, Subbu S. (2013)
This study reports on the release of a novel natriuretic peptide, CD-NP, from an in situ polymer precipitation delivery system. Following extensive screening of in-vitro release profiles, an in-vivo evaluation of the efficacy of the delivery system was carried out in Wistar rats. Gel injection was performed subcutaneously on the back of the rats. A secondary messenger, cyclic Guanosine 3′5′ Monophosphate (cGMP), was tested for verification of CD-NP bioactivity, in addition to direct measurements of CD-NP levels in plasma and urine using a radio-immuno assay. Plasma evaluation showed an elevated level of CD-NP over 3 weeks' duration. Unexpectedly, plasma cGMP level followed a decreasing trend over the same duration despite high CD-NP level. Loss of drug bioactivity was ruled out as a high level of CD-NP and cGMP excretion was observed in the treatment group as compared to baseline readings. This unexpected low-plasma cGMP levels and high-urinary cGMP excretion suggest that there might be other compensatory responses to regulation of the CDNP bioactivity as a result of the high drug dosing. The results stress the importance of assessing the overall bioactivity of released drug (in-vivo) concurrently in addition to measuring its concentrations, to determine the correct release profile.